Control of bovine paralytic rabies in Latin America and the Caribbean - Arellano Sota, C.
(Fr, Es)
Ilus., 39 ref.
Keywords: GANADO BOVINO; RABIA; VIROSIS; ENFERMEDADES INFECCIOSAS; VECTORES; CHIROPTERA; CONTROL DE ENFERMEDADES; VACUNA; AMERICA LATINA; CARIBE; RABIA PARALITICA BOVINA; MURCIELAGOS; REVISTA MUNDIAL DE ZOOTECNIA